Diet preferences of small fishes at Setiu Lagoon, Malaysia - Kassim, Zaleha; Majid, Muhammad Solleh; Mat Alwi, Nur Yahdiyani; Hasnan, Hazwani Hanim (Isaac Scientific Publishing, 2018)
This study aimed to investigate diet preferences of small fishes in a shallow coastal lagoon through analysis of their stomach contents.The 24 hours samplings was done during high tide at selected stations; mangrove areas and seagrass areas, both located at coastal lagoon of Setiu, Terengganu (N5o41.75’ E102o42’ to N5o 42.5’ E 102o41’). The small fishes were caught using seine nets (0.5 cm2), while the zooplanktons were collected using Kitahara zooplankton net (110 microns) then were preserved. All items found in the stomach were compared with the composition of the zooplanktons obtained from the water samples. During the sampling time, 10 species of small fishes were caught. There were higher number of fishes and zooplanktons caught from the seagrass areas than the mangrove areas. Nonetheless, diversity of zooplankton was higher in the mangroves. Overall, the number of harpacticoid was higher than all other food items found in the stomach of fishes caught from both areas despite the high number of calanoid copepods found in the lagoon